PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Azrina Purba (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The purpose of this study is to determine the effect of learning by using a realistic mathematical approach to the ability to understand students' mathematical concepts. This research is a quasi-experimental research. This research was conducted at MTs Islamiyah Medan. The research sample consisted of 50 students, 25 experimental class students, and 25 control class students obtained by cluster random sampling technique in class VII students. The results of the study explained that the average ability to understand mathematical concepts of students who use a realistic mathematical approach is higher than the average ability to understand mathematical concepts of students who use conventional learning. It can be seen from the average posttest score of students' mathematical problem-solving ability of 29.125 in the experimental class and 27.250 in the control class. However, the realistic mathematical approach model in the experimental class was significantly more successful in improving students' understanding of mathematical concept skills compared to conventional methods. Thus the learning of realistic mathematics influences the ability to understand the concepts of mathematical students (tcount = 3.91 ttable = 2.13). The conclusion of this study is that there is a positive influence on realistic mathematical approaches to students' mathematical concept understanding abilities.Keywords: Realistic Mathematics Approach, Understanding of Mathematical Concepts.